DIFFERENCES OF TEMOZOLAMIDE RESPONSE IN GLIOBLASTOMA MULTIFORME: REPORT OF TWO CASES - Djohan Ardiansyah; Vita Kusuma Rahmawati; Sri Andreani Utomo (Callosum Neurology, 2020)
Background: Glioblastoma multiforme (GBM) is about 20% of primary adult brain neoplasms which has poor prognosis; life expectancy is no more than 12 months after the diagnosis. Temozolomide (TMZ) has become GBM standard therapy, combined with the surgery and radio-chemotherapy. Evaluation is important since its relation with the continuity or termination of therapy. Several studies are improving to measure therapy response of GBM. Response Assessment in Neuro-Oncology (RANO) criteria which is published in 2010, became a major criterias to evaluate TMZ response in patients with GBM. This criteria combines clinical manifestation, steroid therapy, and brain magnetic resonance imaging (MRI). Case: We report two GBM cases with standard management. Two women in productive ages and specific clinical manifestations, diagnosed with GBM in left temporal lobes. A 24-year-old woman showed complete response; while a-41-year old one showed progressive response. Discussion: We analyze TMZ response based on RANO criteria. Prognostic factors that differentiate TMZ response in both cases were presence of comorbidity, intratumoral hemorrhage on MRI, and surgery initiation in early diagnosis. Conclusion: Based on RANO criteria and prognostic factors which support TMZ response, the role of adjuvant TMZ become important in standard management of GBM. Keywords: Glioblastoma Multiforme, Response Assessment in Neuro-Oncology, Temozolomide.